2015
DOI: 10.1152/ajplung.00345.2014
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of pulmonary hypoplasia and pulmonary vascular remodeling by antenatal simvastatin treatment in nitrofen-induced congenital diaphragmatic hernia

Abstract: Congenital diaphragmatic hernia (CDH) has a high mortality rate mainly due to lung hypoplasia and persistent pulmonary hypertension of the newborn (PPHN). Simvastatin has been shown to prevent the development of pulmonary hypertension (PH) in experimental models of PH. We, therefore, hypothesized that antenatal simvastatin would attenuate PPHN in nitrofen-induced CDH in rats. The efficacy of antenatal simvastatin was compared with antenatal sildenafil, which has already been shown to improve pathological featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 60 publications
4
38
1
Order By: Relevance
“…We focused primarily on the physiological effects of antenatal sildenafil treatment in DH lambs, so our study is limited by the absence of histological evidence to confirm the morphological and biochemical features underlying the observed physiology. However, the effects of sildenafil on pulmonary vascular development have been well described in other animal models of CDH and correlate well with our current findings. Interestingly, fetal plasma sildenafil concentrations in our lambs immediately prior to delivery (2–5 ng/mL) were similar to those obtained in rats by Mous et al ,.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We focused primarily on the physiological effects of antenatal sildenafil treatment in DH lambs, so our study is limited by the absence of histological evidence to confirm the morphological and biochemical features underlying the observed physiology. However, the effects of sildenafil on pulmonary vascular development have been well described in other animal models of CDH and correlate well with our current findings. Interestingly, fetal plasma sildenafil concentrations in our lambs immediately prior to delivery (2–5 ng/mL) were similar to those obtained in rats by Mous et al ,.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, antenatal treatment with the PDE‐5 inhibitor sildenafil has been shown to attenuate pulmonary vascular abnormalities in both a nitrofen‐induced CDH rodent model and a surgery‐induced CDH rabbit model, which is more clinically relevant in terms of lung development. In these animal studies, antenatal sildenafil treatment increased cGMP and vascular endothelial growth factor expression in lung tissue, increased distal pulmonary vessel density, decreased pulmonary vascular muscularization, reduced right ventricular wall thickness and increased distal airway complexity. However, it is unclear if these improvements in pulmonary vascular structure and biochemistry translate to improved pulmonary hemodynamics after birth.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have performed some studies on the antenatal use of the phosphodiesterase-5 inhibitor sildenafil in different animal models of CDH, showing improvement in alveolarisation and pulmonary vascular development [57][58][59][60][61]. However, the pulmonary pathology in these treated animals did not show complete reversal to the normal lung histology.…”
Section: Treatment Of Pulmonary Vascular Defects In Cdhmentioning
confidence: 98%
“…Mous et al [12] demonstrated that prenatal sildenafil started at a clinically relevant time point decreases lung hypoplasia and attenuates vascular remodeling in nitrofen-induced CDH in rats. Makanga et al [17] reported that antenatal simvastatin presented similar effects as antenatal therapy with sildenafil, improving the pathological features of lung hypoplasia and PH.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, prenatal treatment with sildenafil results in improved pulmonary morphology and increased vessel density associated with evidence of decreased PH [12-16]. Similarly, antenatal maternal administration of simvastatin in experimental nitrofen-induced CDH improves the pathological features of lung hypoplasia and PH, promoting improved lung parenchyma architecture and decreased pulmonary arteriolar remodeling [17]. …”
Section: Introductionmentioning
confidence: 99%